2000
DOI: 10.1002/1097-4652(200009)184:3<356::aid-jcp10>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin regulation during skeletal muscle regeneration

Abstract: Myostatin, a member of the TGF-beta superfamily, is a key negative regulator of skeletal muscle growth. The role of myostatin during skeletal muscle regeneration has not previously been reported. In the present studies, normal Sprague-Dawley and growth hormone (GH)-deficient (dw/dw) rats were administered the myotoxin, notexin, in the right M. biceps femoris on day 0. The dw/dw rats then received either saline or human-N-methionyl GH (200microg/100g body weight/day) during the ensuing regeneration. Normal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 48 publications
5
54
1
4
Order By: Relevance
“…Nevertheless, some studies into the relationship between GH and MSTNs might further elucidate this complex relationship. An inverse relationship between GH and MSTN was found in rat muscle (Kirk et al, 2000) and human muscle cells (Taylor et al, 2001). Some researchers also found that a GH-responsive element was identified to be the upstream of the MSTN promoter region in fish (Roberts and Goetz, 2003;Taylor et al, 2001), which suggested that at the same time GH could regulate MSTN gene transcription and stimulate the GHR gene expression.…”
Section: Genesmentioning
confidence: 97%
“…Nevertheless, some studies into the relationship between GH and MSTNs might further elucidate this complex relationship. An inverse relationship between GH and MSTN was found in rat muscle (Kirk et al, 2000) and human muscle cells (Taylor et al, 2001). Some researchers also found that a GH-responsive element was identified to be the upstream of the MSTN promoter region in fish (Roberts and Goetz, 2003;Taylor et al, 2001), which suggested that at the same time GH could regulate MSTN gene transcription and stimulate the GHR gene expression.…”
Section: Genesmentioning
confidence: 97%
“…For instance, transforming growth factor-b (TGFb) family members control diverse processes in the myoblast and satellite cells ranging from proliferation and fusion to differentiation, and the patterns of expression change dynamically in regenerating muscles to control sequential stages of muscle repair (Kollias and McDermott 2008). Illustrating a switch from an adaptive to a maladaptive mechanism, functional levels of the TGFb family member myostatin, a negative regulator of muscle mass, decline during active regeneration to permit satellite cell activation (Kirk et al 2000;Kocamis et al 2001). However, in chronic myopathic states, myostatin as well as TGFb itself are elevated coincident with fibrosis, and recent interventions to antagonize signaling have been noted to restore muscle function in mouse models of muscular dystrophies (Minetti et al 2006;Cohn et al 2007).…”
Section: Two Roads Diverged In a Wood And I-i Took The One Less Travmentioning
confidence: 99%
“…61 The increase in skeletal muscle myostatin protein levels may be linked with myofiber necrosis, as myostatin levels have been shown to be elevated within necrotic, but not regenerating fibers. 62 Additionally, increased levels of myostatin may contribute to reduced myofiber regenerative potential 58 by inhibiting myoblast proliferation. 63 Future investigations should be aimed at establishing if the alterations in signaling proteins observed in the present study are also implicated in other abnormalities occurring in aged skeletal muscle.…”
Section: Atrophy and Hypertrophy Signaling In Sarcopenia 171mentioning
confidence: 99%